Sustainable Development of Information Systems for Logistics as a Tool to Strengthen the Competitive Ability on Global Markets - Štor, Štor (Naše gospodarstvo/Our economy, 2019)
The main purpose of the article is to motivate experts and researchers in the field of business informatics and logistics to interdisciplinary integration in order to develop a new concept of an information system that will help to strengthen a company’s competitive ability. The article analyzes the research carried out between top managers, strategic managers and managers of logistics in the largest Slovenian companies. Two hundred companies were included in the primary survey; 60 managers were selected in a representative sample and at the end 30 leaders in statistical analysis. We sent questionnaires to our managers via e-mail. The data were processed with the statistical program IBM SPSS Statistics 19, as a method we used linear regression and multiple correlation. With the primary survey, we measured satisfaction of the managers with existing information support for logistics and found that logistical, strategic information professionals need to be even more connected, so that management decisions can then be developed and sustained. On the basis of the obtained data, it can be concluded that sufficient investment of funds in the creation of an appropriate information system fosters the development of business logistics. The originality and value of the article are reflected in the interdisciplinary view of the concept of information support of logistics in the development of new products, in the original connections of various business functions, in the possibility of designing new information solutions and in the sustainable development of new services for the market.